Cassava Biology, Production, and Use - Frediansyah, Andri (IntechOpen, 2021)
Cassava is a staple crop in a large number of countries due to its adaptability to a variety of climatic conditions. It has spread extensively throughout Latin America, tropical Asia, and Sub-Saharan Africa. Cassava, which is well known for its high carbohydrate content, is the third most carbohydrate-rich food after rice and maize. This book discusses the diversity of cassava and its microbiome, cassava cultivation and postharvest practices, as well as crop yield-reducing diseases. Due to its widespread use and market importance, cassava has been subjected to biological and technological intervention to ensure food safety. This book will help readers to gain knowledge about cassava, its biological properties, and some of the strategies and procedures necessary to increase cassava crop output.